Factors that influence school enrolment of children with disabilities in South Africa - Odimegwu, Appolonia N. (My University, 2024)
Background: Since the advent of democracy in South Africa, several programs and policies have been formulated to deal with the needs of disabled children to enable them to enter mainstream society. Nonetheless, despite these policies, disabled children are among the most underprivileged in terms of school access. There are many disabled children who have not been enrolled in the school system. This study explored issues of access to quality education for disabled children in South Africa. The study investigated the factors that influence the school enrolment of children with disabilities in South Africa with the intention of identifying the individual, socioeconomic, household, and community determinants of school enrolment. Data Source and Method: Secondary data from the General Household Survey 2020, extracted from Statistics nesstar was used. The research design is quantitative. The weighted sample size for this study is 198,162 children with disabilities. The dependent variable is the school enrollment of children with disabilities. Bronfenbrenner ecological system theory was the theoretical framework for this study. A three-phase analysis comprising univariate, bivariate, and multivariate analyses was done. Multivariate logistic regression was used to conduct the analysis. Results: It was found that household size, place of residence, province, household income, household own vehicle, and the mother’s employment status are factors that influence school enrollment of disabled children. Children with disabilities from households that own vehicles are more likely to be enrolled in school. The larger the family size (6+), the more likely a disabled child would be enrolled in school. Also, the employment status of the mother influences the school enrolment of children with disabilities. Surprisingly, disabled children residing in rural areas had more chances of enrolling in school than those living in urban areas. Conclusion: The findings underscore the fact that a social ecological model should be used to conduct an in-depth investigation into the enrollment of disabled children in schools. Policy implications are discussed
A research report submitted in partial fulfilment of the requirements for the degree Master of Education by Coursework and research report to the Faculty of Humanities, School of Education, University of the Witwatersrand, Johannesburg, 2023
Keywords: Quality education; Disabled children; School enrolment